Illness trajectory in heart failure: narratives of family caregivers - Carlos Sampaio; Isabel Renaud; Paula Ponce Leão
ABSTRACT Objective: To explore the meaning of being a family caregiver for a relative with advanced heart failure (HF) in their own home, and to gain an understanding of how dignity is upheld in family caregiving contexts. Method: We used a phenomenological-hermeneutical method inspired by the Ricoeurian philosophy. Portuguese caregivers for relatives with advanced HF participated in two reflective interviews over a four-month period. Results: The ten family caregivers enrolled in this study included two daughters and eight spouses with a mean age of 70 years. We identified two main themes: (1) Struggle between inner force and sense of duty; (2) Struggle between feelings of burden and security. Final considerations: People with HF have debilitating symptoms associated with psychological stress, which can burden both them and their family caregivers. Findings support that family caregivers require participation in the planning and execution of their relative's health care.